End User Impacts of Automated Electrochromic Windows in a Pilot Retrofit Application - Eleanor S. Lee; Erin S. Claybaugh; Marc LaFrance (Energy and Buildings, 2012)
Automated electrochromic (EC) windows, advanced thermally-improved window frames, and a dimmable lighting system were installed in a single, west-facing conference room in Washington DC. The EC windows were commercially-available, tungsten-oxide switchable devices, modulated automatically between either fully clear or fully tinted transparent states to control solar gains, daylight, and discomfort glare. Occupants were permitted to manually override the automated EC controls. The system was monitored over a 15-month period under normal occupied conditions. The last six months were used in the analysis. Manual override data were analyzed to assess the EC control system design and user satisfaction with EC operations. Energy and comfort were evaluated using both monitored data and simulations.Of the 328 meetings that occurred over the six month period, the automatic system was manually overridden on 14 or 4% of the meetings for reasons other than demonstration purposes. When overridden, occupants appeared to have switched the individual zones with deliberation, using a combination of clear and tinted zones and the interior Venetian blinds to produce the desired interior environment. Monitored weekday lighting energy savings were 91% compared to the existing lighting system, which was less efficient, had a higher illuminance setpoint, and no controls. Annual performance was estimated using EnergyPlus, where the existing condition met the ASHRAE 90.1-2007 prescriptive requirements except for a higher window U-value. Annual energy savings were 48% while peak demand savings were 35%.
Keywords: buildings energy efficiency; control systems; daylighting; Electrochromic windows; Integrated systems; Intelligent buildings